Položaj nadzornega sveta v času krize - Bratina, Borut (Podjetje in delo, 2013)
The author represents the competences of the supervisory board and the position of its chairperson as prescribed by the corporate legislation. Furthermore, the author presents the influence of the current global economic crisis and the crisis in individual companies on the position of the supervisory board. In common circumstances the supervisory board acquires information about the overall situation of the company which he needs to perform effective supervision, from reports that are prepared and given by the management board. In strained economic circumstances such information does not suffice. The supervision must be more active in its role. Finally the author exposes some German case law, which clearly shows what is expected from duly diligent supervisory board members in time of crisis.
Keywords: ekonomska kriza; finančno poslovanje; gospodarske družbe; nadzorni sveti; pristojnosti